Moving Curve of Civilization - Eid, Salah (Advances in Social Sciences Research Journal, 2021)
One glance to the map of the Earth shows us that the main centers and sub centers of civilization are distributed on the surface of the Earth according to a very accurate geometrical system: the main ones are located on a strait line from Egypt to Greece to western Europe. From Egypt in the ancient times , and from Western Europe in modern times a curve extends to the right and left on which the sub centers are located, this curve moved completely from its northern position in ancient times to its southern position in modern times where one thousand years separates the two ancient and modern stages of civilization, this period had been filled by Greeks and Arabs through which we are going to tell the story of this moving curve between its two ancient and modern positions. Briefly seven hundreds of years had been filled by Greeks : one century in Athena, six centuries in Alexandria of Egypt,( where the curve returned to its southern position), and three centuries by Arabs in Bagdad in Iraq before the third stage of modern civilization began its role in its main center , western Europe.